Positivity - Fredrickson, Barbara 1964- (Crown Publ., 2009)
A psychologist explains how to create a richer, healthier, more fulfilling life through a process called the upward spiral that incorporates innovative techniques for using positivity to influence relationships, health, and work.
Includes bibliographical references (p. 235-266) and index
Keywords: Positive psychology; Lebensführung; Positive Psychologie; Selbstverwirklichung